EXPERIENCE OF THE INTEREST EDUCATION IN DEVELOPMENT OF A SOCIALLY ACTIVE PERSON IN LIEPAJAS CHILDREN AND YOUTH CENTRE (LATVIA) - Klasone, Inta; Klasone, Ineta; Lanka, Svetlana; Lidaka, Anita (European Scientific Journal, ESJ, 2015)
Interest education in Latvia is an essential component of the education system. Formal education is related with school activities, while implementation of interest educational is more flexible. Interest education content has a more practical nature therefore developing specific skills that influence forming of the individual‘s attitudes.The development of interests has a complex and diverse nature and it is an important aspect of personal development. This establishes a special focus on pupil‘s education, development and improvement, as each country‘s future is based on children and youth. At the same time, it can be noted that the opportunities of interest education for personal development has not been properly evaluated. The paper deals with the opportunities of interest education centres in providing self-implementation possibilities in the context of the development of a socially active individual. Practical research was carried out on the basis of Liepaja Children and Youth Centre‘s experience. In order to identify the thematic planning of the centre and its compliance with socially active personality.Involving the students in interest education, it is possible to increase pupils‘ activity and involvement in social processes of city, county and state significance.